Conflicting Institutional Logics in the Religious Context of Islam - Hasibe Aysan (Yönetim ve Organizasyon Araştırmaları Dergisi, 2017)
This paper aims to develop a conceptual framework to explain how organizations may respond in the case of conflict between Islam and other institutional logics. Taking into consideration some theoretical and empirical studies, I propose that there are two main alternative ways for organizations to react in such a conflict: according to the merits of the religion or according to the norms of the field. I argue that the former alternative promotes the protection of religious authenticity whereas the latter promotes the reinterpretation of religious rules and is thus in touch with modern practices. I further offer some ontological and functional aspects of Islam as antecedents of organizational responses.